2007
DOI: 10.1210/en.2007-0300
|View full text |Cite
|
Sign up to set email alerts
|

CD8+CD122+ T Cells, a Newly Identified Regulatory T Subset, Negatively Regulate Graves’ Hyperthyroidism in a Murine Model

Abstract: Graves' disease is a thyroid-specific autoimmune disease mediated by stimulatory autoantibodies against the TSH receptor (TSHR). We have previously shown in our mouse model with adenovirus expressing the TSHR that antibody mediated depletion of CD4(+)CD25(+) regulatory T cells (Tregs) enhances incidence and severity of hyperthyroidism in resistant and susceptible mouse strains, respectively. These data indicate that balance between effector T cells and Tregs is critical for disease development. This study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 36 publications
3
56
1
Order By: Relevance
“…The results from Ag-specific T cell detection in vitro and CD4 T cell depletion in vivo suggested that vWFA2 fused to intein induced vWFA2-specific CD4 T cells, which supported autoantibody production in this model. In some autoimmune diseases, CD8 T cells were shown to modulate autoantibody production (44)(45)(46). However, in both pemphigoid and pemphigus, CD8 T cells were not required for autoantibody production after cell transfer into immunodeficient mice (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…The results from Ag-specific T cell detection in vitro and CD4 T cell depletion in vivo suggested that vWFA2 fused to intein induced vWFA2-specific CD4 T cells, which supported autoantibody production in this model. In some autoimmune diseases, CD8 T cells were shown to modulate autoantibody production (44)(45)(46). However, in both pemphigoid and pemphigus, CD8 T cells were not required for autoantibody production after cell transfer into immunodeficient mice (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…The development of GD is influenced by various genetic and environmental factors and the interactions between them (1). GD pathogenesis is generally characterized by abnormalities in T-cell subsets (2,3), innate immune cells (4), and various cytokines, which ultimately decreases immune tolerance and excessively activates B cells, promoting the production of thyroid stimulating hormone (TSH) receptor antibody (TRAb). The biased activation of helper T (Th) cells has an important role in GD development (5,6) and the imbalance of Th1/Th2 cell immunity may result in a shift toward the Th2-type immune response (7).…”
Section: Introductionmentioning
confidence: 99%
“…17 Moreover, CD8 1 CD122 1 Tregs could suppress other autoimmune diseases in animal models. Saitoh et al 42 found that depletion of CD8 1 CD122 1 T cells increased the incidence of autoimmune Graves' hyperthyroidism in a murine model, suggesting that they play an essential role in suppressing autoimmune hyperthyroidism. CD8 1 CD122 1 and CD4 1 CD25 1 Tregs cooperatively prevented CD4 1 T cell-mediated colitis.…”
Section: Introductionmentioning
confidence: 99%